PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR PADA MATERI STRUKTUR ATOM SISWA KELAS X SMA NEGERI 10 PONTIANAK - Israwati Hasibuan; Cawang Cawang; Dedeh Kurniasih (Jurnal Ilmiah Ar-Razi, 2019)
This study was conducted to determine the differences in student learning outcomes based on the low student learning outcomes which are below the KKM value ≥ 70 and aimed at knowing the magnitude of the influence of the use of cooperative models Student Teams Achievement Division (STAD) with those taught using conventional models of class X class 10 Pontianak SMA on the material of the atomic structure sub protons, neutrons, electrons and isotopes, isobar, isoton. The form of the research used was quasi-experimental research with a pretest-posttest design control group research design. The sample in this study was class XA students as the control class and XB as the experimental class. The data collection technique used was a measurement technique. Data collection tools used were interviews and test results of student learning in the form of essays. The results of statistical tests using the Mann Whitney U-test with α = 5% obtained a probability of <0.05, which meanth that Ho was rejected. These results indicated that there were significant differences between the learning outcomes of class X students of Pontianak State Senior High School on the material of atomic structure sub proton, neutron, electron and isotope, isobar, isoton. The magnitude of the influence of the use of the cooperative model Student Teams Achievement Division (STAD) on the atomic structure material of protons, neutrons, electrons and isotopes, isobars, isotons on student learning outcomes calculated by Effect Size was 0.431 which is categorized as medium. This showed that the use of the cooperative model Student Teams Achievement Division (STAD) type had a categorical influence on the learning outcomes of class X students of SMA Negeri 10 Pontianak on the material of atomic structure sub proton, neutron, electron and isotope, isobar, isoton.